ANALISIS PENGARUH LAYANAN, HARGA, DAN KUALITAS PRODUK PAKAIAN WANITA YANG DIJUAL SECARA ONLINE MELALUI GROUP BLACKBERY MESSENGER TERHADAP MINAT BELI KONSUMEN (STUDI KASUS MAHASISWI STIE MANDALA JEMBER) - Putri Dewi Lestari; Muhammad Firdaus; Tamriatin Hidayah (STIE Mandala Jember, 2013)
This study aims: (1) to determine the effect of service, price, and quality of womenswear products simultaneously to consumers to buy. (2) to determine the effect of the service, price, and quality of womenswear products partially on consumers to buy. Sampling technique are used snowball sampling. Total sample were 60 respondents who transact womenswear products through BlackBerry Messenger (BBM). The analysis used multiple regression. The results showed: (1) service, price, and quality of womenswear sold online through Blackberry messenger group simultaneously significantly affect consumer buying interest. (2) Partially, only price variable that significantly influence the consumers to buy.